Prospects for the use of leaves and inflorescences of fireweed (Chamaenerion angustifolium (L.) Scop.) as a medicinal plant material (review) - M. S. Antonenko; E. L. Malankina (Овощи России, 2022)
Relevance. Currently pharmaceutical industry, food industry and chemical laboratories demonstrate an increasing interest in natural plant sources, including Chamaenerion angustifolium. Modern researches reveal more and more medicinal properties of this plant. For this reason, the demand for the use of fireweed as a medicinal plant, especially its leaves and flowers, is very high. It means, that the study of biological properties, chemical composition, ecological and landscape features of fireweed is of scientific and practical interest.Methods. This article contains information from literary sources about pharmaceutical, chemical, biological, ecological and geographical studies of Chamaenerion, its results and recommendations. Obtained from other researches information was systematized by research topics and presented in a logical sequence.Results. The issues of using this plant in medicine and food industry are also considered here, along with the discription of collecting natural fireweed problems and the mail ways of cultivating this species. The modern condition of fireweed research is shown, a detailed analysis of fireweed biological and ecological characteristics is carried out and on this basis, the main directions for further work on the introduction of Chamaenerion into culture for its more complete and rational use in medicine and in the food industry are outlined in this article. The article presents an analysis of the problems that arise during the introduction, in particular, the improvement of vegetative reproduction techniques, the selection of populations promising in terms of the phenolic compounds content and the possibility of target compounds content in plants by the exogenous regulation.Conclusion. Despite the presence of a relatively large quantity of works devoted to Chamaenerion, some research topics are poorly covered. For example, the topic of cultivation and the use of growth regulators. The most promising directions for the future study of Chamaenerion are indicated in this article.